Pengaruh Penyimpanan dan Pemanasan Terhadap Perubahan Ukuran Nanopartikel Parfum Campuran Minyak Royal Musk dan Minyak Atsiri Lili yang Disintesis Menggunakan Surfaktan Polimer PEG-40 HCO - Winarti, Ratu Sesillia; Saragih, Horasdia (Jurnal Fisika Unand, 2025)
The purpose of this study was to produce perfume nanoparticles made from a mixture of royal musk oil and lily essential oil that can be dispersed in an aqueous medium and to investigate their size stability after storage and heating. The perfume nanoparticles were synthesized using an atomization technique with PEG-40 HCO as a surfactant, and their stability was evaluated through storage for up to 120 days and heating at temperature up to 45 °C. The results showed that storage for 120 days significantly increased the average particle diameter and its standard deviation. Heating also caused a significant increase in nanoparticle size. These findings indicate that the size of the perfume nanoparticles was not stable, as the zeta potential and the presence of PEG-40 HCO surfactant could not provide sufficient electrostatic and steric protection. Consequently, coalescence and Ostwald ripening occurred in the nanoparticles.